Covered Stent as an Optional Endovascular Approach to Treat Direct Carotid-Cavernous Fistula: A Case Report - Annisa Bunga Nafara; Ahmad Sulaiman Alwahdy; Elsa Primadona Sulfana Putri (Neurointervention Working Group of Indonesian Neurological Association, 2025)
Highlight: Direct CCF often mimics neuro-ophthalmic disorders, causing delayed diagnosis Covered stent is effective as a primary endovascular option for dCCF Risks of covered stent placement are stenosis, thrombosis and branch occlusion ABSTRACT Introduction: The use of covered stents has emerged as a treatment option for direct Carotid Cavernous Fistula (dCCF). However, it has not been routinely adopted in Indonesia. We report the first case in Indonesia of direct traumatic CCF successfully treated with a covered stent as the first-line endovascular therapy. Case: A 21-year-old woman with blurred vision, diplopia and swelling in the right eye, cranial nerves III and VI palsy with a history of traumatic fall two months prior. Digital Subtraction Angiography confirmed the presence of a right-sided direct carotid-cavernous fistula. Embolization was performed using a 3.5x16 mm Bentley covered stent at the fistula site. Direct embolization confirmed a type A right CCF resulted in complete obliteration and previous complaints were significantly reduced. Conclusion: Endovascular therapy with covered stents offers a promising treatment option for CCF, providing vessel patency and effective fistula occlusion. But the risk of complications should be considered.